behavioral assessment of metrics in manet routing protocols under realistic environments - Venkata Ramana Gupta, N.; M. Ramesh, Dr. (International Journal of Engineering and Technology, 2018)
A Network in which nodes communicate without any centralized control or infrastructure can be considered as Mobile Ad-hoc Network (MANET.).Data is exchanged in multi hops via wireless channels .For the smooth exchange of information, we need routing protocols for effective and timely delivery of the message. Ad hoc routing protocols AODV, DSDV, DSR, TORA have several metrics like Throughput, End to End Delay Normalized Route Load, Packet Delivery Ratio, Energy Efficiency, the number of nodes, fidelity, distance, etc., to Asses. We have compared routing protocols basing on these metrics and the performance is analyzed and graphs have been generated on Network Simulator (NS-2, NS-3).Â Â